2022
DOI: 10.3389/fvets.2022.998344
|View full text |Cite
|
Sign up to set email alerts
|

Detection and investigation of atypical porcine pestivirus in a swine production system

Abstract: A commercial farrow-to-finish farm was suspicious of atypical porcine pestivirus (APPV) after observing clinical signs of congenital tremors (CT) and splay leg (SL) of newborn pigs. If introduced onto the farrow-to-finish, the two potential routes of introduction could be through replacement gilts or incoming semen doses. Therefore, this study aimed to determine the prevalence of clinical APPV within the sampled population, identify the route of APPV introduction to this system, and determine prevalence of det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…In the literature, there are reports of co-morbidity between CT type A-II and splay leg following infection with APPV Gatto et al 2018b;Houston et al 2022). Thus, APPV has by some been suggested as one causative agent of splay leg, but the causality between APPV and splay leg is to this date not established .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the literature, there are reports of co-morbidity between CT type A-II and splay leg following infection with APPV Gatto et al 2018b;Houston et al 2022). Thus, APPV has by some been suggested as one causative agent of splay leg, but the causality between APPV and splay leg is to this date not established .…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that APPV may be transmitted transplacentally as well as horizontally Folgueiras-González et al 2020b;Houston et al 2022). However, the exact routes of horizontal transmission are not yet fully understood.…”
Section: Routes Of Appv Transmission and Pathogenesismentioning
confidence: 99%
See 3 more Smart Citations